Effectiveness of Service Marketing Strategies on Student Enrollment: Evidence from United College (United Journal of Interdisciplinary Studies, 2024)
As competition among colleges and universities intensifies, effective service marketing strategies play a critical role in attracting prospective students and increasing enrollment numbers. In this context, this study aims to analyze the effectiveness of service marketing strategies on student enrollment of United College (UC). Theoretical underpinnings from the 7Ps marketing mix theory of Philip Kotler, a robust framework, is used to understand the influence of marketing strategies on student enrollment at UC. Through quantitative research approach, descriptive and correlational research design, and data collected from 122 enrolled students across various programs, the study examined seven specific marketing strategies: product offerings, pricing, place/location, promotion, process, people, and physical evidence. It is found that product offerings, pricing, place, promotion, and people strategies had significant positive impacts on student enrollment, as indicated by their respective t-values and p-values. However, process/admission procedures and physical evidence strategies did not demonstrate significant impacts on enrollment. Therefore, effective implementation of service marketing strategies, notably product offerings, pricing, place, promotion, and people, is pivotal for colleges like UC to bolster student enrollment, underlining the importance of strategic marketing in higher education competitiveness.